Amplification of the matrix gene of RBOK vaccine strain of rinderpest virus (RPV) by polymerase chain reaction and cloning into TOPO® XL cloning vector - Azkur, AK; Bolat, Y; Doymaz, MZ (Scientific Technical Research Council Turkey, 2003)
In this study, the matrix (M) gene of the RBOK vaccine strain of rinderpest (RPV) was amplified by polymerase chain reaction (PCR) and cloned into TOPO(R) XL cloning vector. For this purpose, Vero cells were infected with the RBOK vaccine strain of RPV and total RNA was obtained from the infected cells. cDNA of the matrix gene was obtained by reverse transcription from the total RNA. Amplification of the cDNA with PCR was achieved by using the M gene specific primer and PCR products of the M gene were directly ligated into the TOPO(R) XL cloning vector and this recombinant plasmid DNA transformed into JM109 competent E. coli cells. To determine the presence of the M gene in the recombinant plasmid pTOPO XL, both PCR and restriction enzyme digestion assays were performed.
Si?ir vebasi virüsü RBOK aşi suşu matriks geninin polimeraz zincir reaksiyonu ile ço?altilmasi ve TOPO® XL klonlama vektörüne yerleştirilmesi
Keywords: rinderpest; matrix gene; cloning